Germany : Memories of a Nation - MacGregor, Neil
"Germany is unlike any other country in the world. But how much do we really know about it, and how do its people understand themselves? In Germany: Memories of a Nation, Neil MacGregor -- director of the British Museum and author of A History of the World in 100 Objects -- presents the stories of a nation through a collection of thirty objects and touchstones. From coins and crowns to fairytales and philosophers, MacGregor presents the inventions, ideas, and icons that comprise the many identities of the German people. Germany: Memories of a Nation is a view of this complex and fascinating country like no other"--